"It burns her more than it burns for me": The sibling subsystem in the context of child physical abuse as portrayed by children during forensic interviews. (October 2021) - Katz, Carmit; Tener, Dafna
Abstract: Background: The sibling subsystem is a central and potentially protective factor for children. Nevertheless, in the context of child abuse, it remains surprisingly understudied. Objective: The current study was designed to examine how children referred to a forensic interview following suspected physical abuse experienced and perceived the sibling subsystem. Participants and setting: The sample included 60 forensic interviews with children, aged 4 to 14. Each child had at least one sibling and referred to this sibling in the context of the abuse they experienced. Methods: Thematic analysis was carried out on the narratives provided by the children. Several steps were taken to ensure the trustworthiness of the study, with four criteria: credibility, transferability, dependability, and confirmability. Results: The main theme identified was physical abuse as a familial routine. This abusive routine was sometimes perceived as normal and sometimes traumatic, with descriptions of fear and physical pain. The children addressed the various figures in this abusive routine. When these horrific daily experiences were elaborated on, the children often captured the sibling subsystem as a source of security, comfort and protection. Moreover, the children's language often communicated the siblings' bond, referring to "we" and "us." Within a few narratives, a split between the siblings was identified, which appeared to be a strategy of self-protection by going against their siblings. Conclusion: The current findings join the recent accumulating evidence with respect to the centrality of the sibling subsystem in the experiences and consequences of child abuse. It is imperative to advance practitioners' knowledge and interventions to better adapt to the central role of the sibling subsystem in the context of child abuse.